Cáceres y el Contrato Grace: sus motivaciones - Pereyra Plasencia, Hugo (2016)
The Grace Contract, signed in 1888 between the government of President Andrés A. Cáceres and a British bondholders club of Peru’s foreign debt,was presented by its contemporary critics both as an instrument against na-tional interests and a corrupt transaction. This article makes a critical ap-preciation of both assessments. Based on documents from that period, thisarticle argues that, in promoting the Grace Contract, Cáceres was motivated, to a significant extent, by the need to obtain resources to pay a compensationof ten million pesos to Chile under the Ancón Treaty, in case Peru won theTacna and Arica plebiscite envisaged for 1894.